2003
DOI: 10.1111/j.1745-4514.2003.tb00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Sorghum Distillery Residue on Hematological Characteristics of Cultured Grey Mullet (Mugil Cephalus)?an Animal Model for Prescreening Antioxidant and Blood Thinning Activities

Abstract: The sorghum distillery residue (SDR) has been an underutilized by‐product with estimated production of 150 ton/day in Kinmen, Taiwan. The objective of this study was to test for any physiological effects of SDR, thus to utilize it as a nutraceutical feed ingredient in diets for cultured fish. Hot air‐dried, wet, and dehulled‐wet sorghum distillery residue showed 63%, 90% and 97% inhibition of the hemoglobin‐catalyzed oxidation of linoleic acid compared to soybean (13%) and rice bran (78%). The feed formulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
(9 reference statements)
2
27
0
Order By: Relevance
“…Moreover, tannin not only affected the protease activity, but also inhibited comparatively lipase activities to a greater extent and amylase activities to a lesser extent. Lee and Pan (2003) indicated a non-competitive mixed-type inhibition of in vitro trypsin activity from grey mullet (Mugil cephalus) by tannin which may throw some light on possible inhibitory mechanism of such compound. Limited literature on this particular issue suggests that more effort should be given to gain a better insight to find out the mechanism of tanninmediated inhibition of digestive enzymes of fish and its probable effect at the physiological level.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, tannin not only affected the protease activity, but also inhibited comparatively lipase activities to a greater extent and amylase activities to a lesser extent. Lee and Pan (2003) indicated a non-competitive mixed-type inhibition of in vitro trypsin activity from grey mullet (Mugil cephalus) by tannin which may throw some light on possible inhibitory mechanism of such compound. Limited literature on this particular issue suggests that more effort should be given to gain a better insight to find out the mechanism of tanninmediated inhibition of digestive enzymes of fish and its probable effect at the physiological level.…”
Section: Discussionmentioning
confidence: 98%
“…Lee and Pan (2003) demonstrated that dietary tannin-sorghum distillery residues inhibited 63-97% of hemoglobin-catalyzed oxidation of linoleic acid in cultured mullet fish compared to soybean (13%) and rice bran (78%). The authors also found that the sorghum residues significantly improved blood-thinning and erythrocyte membrane integrity of the fish blood cells during winter, thus maintaining normal blood fluidity and preventing RBC hemolysis induced by H 2 O 2 .…”
Section: Sorghum and Cardiovascular Diseasementioning
confidence: 98%
“…There may be an anticoagulant effect of sorghum tannins, yet to be tested in humans, as evidenced in cultured mullet fish that were fed tannin-containing sorghum distillery residues. (170) The sorghum residue significantly improved blood thinning and erythrocyte membrane integrity of the fish blood cells in cooler water temperatures over the winter months, enabling normal blood viscosity and prevention of red blood cell hemolysis induced by typical oxidation processes. The authors suggest that the antioxidant activity of the tannins and polyphenols present in the sorghum residue contributed to the prevention of red blood cell hemolysis.…”
Section: Effects On Serum Lipidsmentioning
confidence: 99%